Global REACH 2018: Andean highlanders, chronic mountain sickness and the integrative regulation of resting blood pressure. Issue 1 (14th May 2020) - Simpson, Lydia L.; Meah, Victoria L.; Steele, Andrew R.; Gasho, Christopher; Howe, Connor A.; Dawkins, Tony G.; Busch, Stephen A.; Oliver, Samuel J.; Moralez, Gilberto; Lawley, Justin S.; Tymko, Michael M.; Vizcardo‐Galindo, Gustavo A.; et al.
Abstract : New Findings: What is the central question of this study? Does chronic mountain sickness (CMS) alter sympathetic neural control and arterial baroreflex regulation of blood pressure in Andean (Quechua) highlanders? What is the main finding and its importance? Compared to healthy Andean highlanders, basal sympathetic vasomotor outflow is lower, baroreflex control of muscle sympathetic nerve activity is similar, supine heart rate is lower and cardiovagal baroreflex gain is greater in mild CMS. Taken together, these findings reflect flexibility in integrative regulation of blood pressure that may be important when blood viscosity and blood volume are elevated in CMS. Abstract: The high‐altitude maladaptation syndrome chronic mountain sickness (CMS) is characterized by excessive erythrocytosis and frequently accompanied by accentuated arterial hypoxaemia. Whether altered autonomic cardiovascular regulation is apparent in CMS is unclear. Therefore, during the 2018 Global REACH expedition to Cerro de Pasco, Peru (4383 m), we assessed integrative control of blood pressure (BP) and determined basal sympathetic vasomotor outflow and arterial baroreflex function in eight Andean natives with CMS ([Hb] 22.6 ± 0.9 g·dL −1 ) and seven healthy highlanders ([Hb] 19.3 ± 0.8 g·dL −1 ). R–R interval (RRI, electrocardiogram), beat‐by‐beat BP (photoplethysmography) and muscle sympathetic nerve activity (MSNA; microneurography) were recorded at rest and during pharmacologically induced changes in BP (modified Oxford test). Although [Hb] and blood viscosity (7.8 ± 0.7 vs . 6.6 ± 0.7 cP; d = 1.7, P = 0.01) were elevated in CMS compared to healthy highlanders, cardiac output, total peripheral resistance and mean BP were similar between groups. The vascular sympathetic baroreflex MSNA set‐point (i.e. MSNA burst incidence) and reflex gain (i.e. responsiveness) were also similar between groups (MSNA set‐point, d = 0.75, P = 0.16; gain, d = 0.2, P = 0.69). In contrast, in CMS the cardiovagal baroreflex operated around a longer RRI (960 ± 159 vs . 817 ± 50 ms; d = 1.4, P = 0.04) with a greater reflex gain (17.2 ± 6.8 vs . 8.8 ± 2.6 ms·mmHg −1 ; d = 1.8, P = 0.01) versus healthy highlanders. Basal sympathetic vasomotor activity was also lower compared to healthy highlanders (33 ± 11 vs . 45 ± 13 bursts·min −1 ; d = 1.0, P = 0.08). In conclusion, our findings indicate adaptive differences in basal sympathetic vasomotor activity and heart rate compensate for the haemodynamic consequences of excessive erythrocyte volume and contribute to integrative blood pressure regulation in Andean highlanders with mild CMS. Abstract :